The Problem of Grapho-phonological Discrepancy in the Pronunciation of the Yoruba User of English. - Fatusin, Stephen Akinnifesi (Obafemi Awolowo University, 2018)
This work attempts to determine the magnitude of the problem posed to Yoruba L2 learners of English by the inconsistent manner in which English words are represented orthographically and the discrepancy between the way English words are pronounced and the way they are spelt. Information collected from the pronunciation and writing of some secondary school level learners of English serves as data for this work.